Through the portal. On writing Ellwood - a modern fantasy novella - Ásrún Ester Magnúsdóttir 1988- (2012)
This final assignment is a result of a Creative Writing course taught by Anna Heiða Pálsdóttir at the English Department in the University of Iceland, fall of 2011. The assignment consists of a novella, Ellwood, and a report on the writing process. The novella is around 30,000 words and the report about 8,500 words. Ellwood is a fantasy revolving around Erin Ellwood, a girl in her early twenties, who suddenly finds herself in the middle of a fairy tale as she is pulled form her everyday life into the amazing world of Asria. She discovers that she is destined for a role in this parallel world, where her origins lie. It is the place from where Grimm fairy tales took place, a magical world where anything can happen. In the story I apply many of the known fairy tale elements and hope that I have managed to create a believable paralleled universe. When writing fantasy almost anything is permissible yet there was always that thin line of not going so far as to lose the reader’s “suspension of disbelief.” The report explains how the idea for Ellwood came into being, how it was created, how it was finished, then edited, rewritten, edited again and finalized. It describes how I relied on famed authors and experienced editors to help me with my writing, mostly by using textbooks on writing by Stephen King and Sol Stein. To understand the contents of the report fully I go out from the assumption that the reader has read the novella before going on to the essay. It is my desire that this final project does not only show my skill as a fiction writer but also my skills in writing creatively in another language than my own, English.